An improved Grey Wolf algorithm for optimal placement of unified power flow controller. (November 2022) - Reddy, K. Manoz Kumar; Rao, A. Kailasa; Rao, R. Srinivasa
Highlights: Exploits the advanced GW-PUE model for optimal placement of UPFC to achieve OPF. Presents GW-PUE for resolving placement, minimization of power loss and cost. T-WOA based loading strategy is better than conventional models. Abstract: Most crucial techniques for power system operation as well as control is Optimal Power Flow (OPF) that establishes the lowest operating costs and keeps the control variables within safe ranges. Furthermore, bus voltage and power flow across a power system are controlled by a device called a Unified Power Flow Controller (UPFC) and it is one of the most promising Flexible AC Transmission Systems (FACTS) devices for load flow control. Due to the necessary adjustments to take into account the UPFC characteristics, solving optimal power flow (OPF) problems with UPFC is a crucial and challenging task. Hence, this work intends to introduce a new Grey Wolf with Populace-based Update Evaluation (GW-PUE) algorithm for optimal placement of UPFC to achieve OPF.Different objective functions like minimization of power loss, voltage profile deviation and UPFC cost are consideredfor solving the placement problem. Moreover, the adoptedapproach is an improved form of the traditional Grey Wolf Optimization (GWO).At last, the adopted model is tested on the standard IEEE 5, IEEE 14 as well as IEEE 30 bus system. The performance of the suggested work is contrasted with extant methods in terms ofvarious measures. Especially, thecomputation time of the adopted GW-PUE method in IEEE 5 bus system is 59.61%, 14.85%, 1.33%, and 16.29% higher than the existing FF-CS, BBO, FF, and MSSA methods, respectively.